TIPOLOGI-MORFOLOGI INTERIOR RUMAHTINGGAL DIBALUWARTI SURAKARTA - Sulistyani, Harmilyanti (Institut Seni Indoensia Surakarta, 2010)
House as a shelter relates with the life style in community. On the other hand, the environment conditions influence the life style and the interior of the house. Those conditions occur in Baluwarti Surakarta, the settlement which is placed surrounding the Surakarta Palace. The settlement has a chain with the history of Surakarta Kingdom, at the moment it has changed because of the changes of social culture in their community. Architecture has diversity and uniformity to describe the objet group based on their basic property by sorting or classifying their diversity and uniformity. Typology is used to categorize the formal structure in each architectural object, furthermore, morphology has a function to see and interpret the development of design in their environment especially interior design. Settlement in Baluwarti has a unique interior because of the changes of people who use it.Baluwarti community, in the early, was Javanese people who had their own vision about house. Nowadays,the community changes are more complex than before and that it causes the shape and form of the environment development. The result of typology and morphology are important for the community. It can be used to make the prototype which can be useful for the conservation of the Baluwarti environment. Keywords: Baluwarti, typology, morphology, interior, home living